Deficit Threshold Optimization of an Automatic Transfer Switch for Hybrid Grid-Photovoltaic Systems in Tropical Climates - Syamsyarief Baqaruzi; Cuk Supriyadi Ali Nandar; Ali Muhtar; Muhammad Rizky Hikmatullah; Norzanah Rosmin (JET (Journal of Electrical Technology), 2026)
The rising demand for dependable power supply in tropical areas, characterized by frequent grid instability, requires the use of automated transfer switches (ATS) in hybrid photovoltaic (PV)-grid systems. This study assesses the efficacy of an Arduino Mega 2560-based Automated Testing System (ATS) coupled with a 100 Wp polycrystalline photovoltaic panel and a 12 V 100 Ah battery in the tropical climate of Lampung, Indonesia, over a span of 15 consecutive days in January. The process encompasses hardware design, the construction of a control algorithm based on a multi-objective cost function incorporating risk factors, field data gathering, and MATLAB simulation. The findings indicate that the system attains 80% grid independence based on day count and exceeds 95% based on total energy, accompanied with a minimal switching frequency of 0.2 occurrences per day, signifying stable operation devoid of chattering. A significant contribution is the optimization of the shortfall threshold: adjusting the threshold from 0 Wh to –10 Wh decreases grid reliance from three days to one day, enhancing PV utilization from 80% to 93.3% without adding battery capacity. The relationship between irradiance and photovoltaic energy is robust (r = 0.94, R² = 0.88), with an average system efficiency of 10.04%, which is plausible for polycrystalline panels in hot, humid environments, including cable, inverter, and heat losses. The boxplot analysis verifies the absence of overlap between energy balances on photovoltaic days and grid days, hence affirming the reliability of ATS judgments. In conclusion, the suggested ATS featuring an adjustable deficit threshold is an economical and dependable option for telecommunication infrastructure in tropical developing areas.